2019
DOI: 10.2174/1566524019666190405120137
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL-33 Level and IL-33, IL1RL1 Gene Polymorphisms in Asthma and Multiple Sclerosis Patients

Abstract: Background: Asthma is a chronic and complex inflammatory disease of the respiratory tract. Also, multiple sclerosis (MS) is a chronic inflammatory demyelinating disease of the central nervous system. Against this background, IL-33 and IL1RL1 play a critical role in autoimmune and inflammatory disorders. Here, we explored the IL-33 serum level and two potential genetic variants in the IL33 gene and its receptor in Iranian asthma and MS patients. Results: The level of IL33 was significantly higher in asthma an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Our present findings indicate elevated serum IL-33 protein levels in CRSwNP patients compared to control. Previous studies have also confirmed elevated IL-33 serum level in asthma patients [ 54 ].…”
Section: Discussionmentioning
confidence: 57%
“…Our present findings indicate elevated serum IL-33 protein levels in CRSwNP patients compared to control. Previous studies have also confirmed elevated IL-33 serum level in asthma patients [ 54 ].…”
Section: Discussionmentioning
confidence: 57%
“…It is released to alert the immune system by first‐line cells, such as tissue epithelial cells, following exposure to exogenous stimuli, including allergens . Importantly, high levels of serum IL‐33 and IL‐33 receptor genetic polymorphism were found in patients with multiple sclerosis, suggesting a relevant role of this cytokine in the pathogenesis of autoimmune disorders . However, our asthma patients were without history of autoimmune diseases that could influence the results.…”
Section: Discussionmentioning
confidence: 85%
“…In addition to REGN3500, etokimab represents a second clinically applicable anti-IL-33 antibody, whose suppressive in vivo effect on the function of IL-33 has successfully been validated in phase 1 and phase 2a clinical trials (143). As the alarmin IL-33 represents a well-established promotor of the bone marrow-tolung recruitment of ILC2s under inflammatory conditions and also serves as a key activating cytokine for pulmonary ILC2 pools (125,126), its antibody-mediated blockade can be expected to relevantly dampen the local involvement of ILC2s in the induction or maintenance of lung inflammation. Due to the rather broad expression profile of the IL-33 receptor ST2 on different immune cell subtypes, targeting IL-33 signaling does not represent an ILC2-specific strategy and can more be seen as a global approach to efficiently block type 2 immunity, including also marked inhibitory effects on lung infiltrating Th2 cells, eosinophils, mast cells and macrophages (144)(145)(146)(147)(148).…”
Section: Discussion Of Clinical Implicationsmentioning
confidence: 99%
“…Experimental induction of allergic lung inflammation was found to result in a decreased ILC2 frequency in the bone marrow, while the number of pulmonary ILC2s increased subsequently, strongly implicating a targeted ILC2 migration from the bone marrow towards the inflamed tissue site ( 124 ). In this context, it was interesting to learn that the IL-1 family member IL-33, whose serum levels are markedly elevated in asthma patients ( 125 ), does not only function as a key activator of ILC2s in peripheral organs, but also crucially impacts on the inflammation-triggered egress of ILC2s from the bone marrow and their subsequent lung-directed hematogenous migration ( 126 ). Indeed, it could be demonstrated in vivo that the intravenous delivery of recombinant IL-33 into wild type mice resulted in a decreased total number of ILC2 precursor cells in the bone marrow, while the de novo generation of ILC2 precursor cells in the bone marrow turned out to be independent from IL-33 signaling ( 126 ).…”
Section: Numeric Regulation Of Local Ilc2 Pools At Inflamed or Fibrotic Pulmonary Tissue Sites By Ilc2 Recruitment And Traffickingmentioning
confidence: 99%